2018
DOI: 10.1002/mbo3.780
|View full text |Cite
|
Sign up to set email alerts
|

Biases in the metabarcoding of plant pathogens using rust fungi as a model system

Abstract: Plant pathogens such as rust fungi (Pucciniales) are of global economic and ecological importance. This means there is a critical need to reliably and cost‐effectively detect, identify, and monitor these fungi at large scales. We investigated and analyzed the causes of differences between next‐generation sequencing (NGS) metabarcoding approaches and traditional DNA cloning in the detection and quantification of recognized species of rust fungi from environmental samples. We found significant differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…For instance, Erysiphe necator, the causal agent of grapevine powdery mildew, was significantly more abundant in conventional than in organic plots. These results are consistent with visual assessments of disease symptoms, indicating that, despite their numerous biases, metabarcoding data do contain some quantitative information useful for monitoring plant disease development (Sapkota et al, 2015;Jakuschkin et al, 2016;Makiola et al, 2018). Several yeast strains, assigned to the genera Vishniacozyma, Sporobolomyces and Filobasidium, were significantly more abundant in organic plots.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, Erysiphe necator, the causal agent of grapevine powdery mildew, was significantly more abundant in conventional than in organic plots. These results are consistent with visual assessments of disease symptoms, indicating that, despite their numerous biases, metabarcoding data do contain some quantitative information useful for monitoring plant disease development (Sapkota et al, 2015;Jakuschkin et al, 2016;Makiola et al, 2018). Several yeast strains, assigned to the genera Vishniacozyma, Sporobolomyces and Filobasidium, were significantly more abundant in organic plots.…”
Section: Discussionsupporting
confidence: 78%
“…It is worth noting that the composition of the protist community in female and male alates did not differ significantly, a general result that allowed us to estimate α values of protists based on their frequency among the 14 alates (seven females and seven males) studied per colony. Overall, our analyses suggested that α values have been underestimated because of the detection limit of metabarcoding (Coissac, Riaz, & Puillandre, ; Hatzenbuhler, Kelly, Martinson, Okum, & Pilgrim, ; Makiola et al, ; Port et al, ). Results of qPCR demonstrated the presence of TgA in workers from colonies in which our deep sequencing approach of the 18S rRNA gene did not allow detection of a single read assigned to this protist species in the pool of worker guts.…”
Section: Discussionmentioning
confidence: 82%
“…Such pathogens often remain largely concealed until the next disease outbreak. However, these pathogens can be detected using DNA‐based approaches such as metabarcoding (Makiola et al, ; Merges, Bálint, Schmitt, Böhning‐Gaese, & Neuschulz, ). Hence, DNA‐based approaches allow a holistic picture of potential plant pathogen communities.…”
Section: Introductionmentioning
confidence: 99%